Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.26420/annhematoloncol.2017.1161
|View full text |Cite
|
Sign up to set email alerts
|

Non-Conventional Pain Management for Sickle Cell Disease

Abstract: Sickle cell disease is a congenital blood disorder affecting hemoglobin molecule. It leads to a rigid, sickle like shape red blood cell. Most people with sickle cell disease have severe painful episodes called vaso-occlusive crises. However, the frequency, severity, and duration of these crises vary tremendously. The pain is classified into two types, nociception pain which is intact peripheral or central nervous system and neuropathic pain which is initiated by dysfunction of the peripheral or central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Furthermore, a higher percentage of adults with SCD experience chronic, debilitating pain which may prompt them to seek alternative means of pain control. 9,11,26 The use of Non-steroidal anti-inflammatory drugs (NSAIDs) as the medication for pain relief were in the majority (47.0%) in this study, which is not surprising, given its proven efficacy and recommendation for use in mild to moderate painful episodes. 3,12,15,16 On the other hand, it was found that massage was the most frequently used CAM among the respondents (50.0%).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Furthermore, a higher percentage of adults with SCD experience chronic, debilitating pain which may prompt them to seek alternative means of pain control. 9,11,26 The use of Non-steroidal anti-inflammatory drugs (NSAIDs) as the medication for pain relief were in the majority (47.0%) in this study, which is not surprising, given its proven efficacy and recommendation for use in mild to moderate painful episodes. 3,12,15,16 On the other hand, it was found that massage was the most frequently used CAM among the respondents (50.0%).…”
Section: Discussionmentioning
confidence: 62%
“…[1][2][3] Amongst other complications, persons living with SCD experience pain which has been found to be the most consistent and characteristic feature. [9][10][11] The spectrum of clinical expression is however heterogenous, varying in intensity, frequency, duration and affected sites. 3,9,12 Pain in SCD is classified as episodic (acute) or persisting (chronic).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations